2020
DOI: 10.1039/d0ra01548b
|View full text |Cite
|
Sign up to set email alerts
|

A molecular electron density theory study of the participation of tetrazines in aza-Diels–Alder reactions

Abstract: The reactions of eight tetrazines of increased electrophilic character with nucleophilic tetramethyl ethylene (TME) and with electrophilic tetracyanoethylene (TCE) have been studied using Molecular Electron Density Theory. These reactions are domino processes comprising an aza-Diels-Alder (ADA) reaction followed by an extrusion of molecular nitrogen, yielding a dihydropyridazine. Analysis of the conceptual DFT (CDFT) indices showed an increase of the electrophilicity and a decrease of the nucleophilicity of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 63 publications
12
135
0
Order By: Relevance
“…Thus, this 32CA reaction is classified as FEDF reaction. [18] Note that this classification of the organic reactions based on the flux of the GEDT is more accurate than that based on the Sustmann's MO based classification, [22] since Sauer categorised the non-polar 32CA reaction with cyclooctyne 17 as "LUMO dipole -HOMO dipolarophile -controlled". [10] This comparative study indicates that the high reactivity shown by experimental cyclooctyne 17 is a consequence of the strain present in this cycloalkyne, which experience a non-polar reactivity.…”
Section: Study Of the Reaction Paths Associated With 32ca Reactions Bmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus, this 32CA reaction is classified as FEDF reaction. [18] Note that this classification of the organic reactions based on the flux of the GEDT is more accurate than that based on the Sustmann's MO based classification, [22] since Sauer categorised the non-polar 32CA reaction with cyclooctyne 17 as "LUMO dipole -HOMO dipolarophile -controlled". [10] This comparative study indicates that the high reactivity shown by experimental cyclooctyne 17 is a consequence of the strain present in this cycloalkyne, which experience a non-polar reactivity.…”
Section: Study Of the Reaction Paths Associated With 32ca Reactions Bmentioning
confidence: 98%
“…The analysis of the natural charges [21] shows that AYs 13a and 18 present an identical electronic distribution at the core framework. While the C1 and N2 centres are negatively charged by ca -0.19 (13a) and -0.21 (18), and -0.26 (13a) and -0.28 (18) e, respectively, the C3 carbon is positively charged by 0.25 e in both AYs. This charge distribution is a consequence of the presence of the two EW -CN groups at the C1 carbon, which strongly polarize the electron density towards the C1 carbon.…”
Section: Elf and Npa Analysis Of The Electronic Structures Of Ay 13a mentioning
confidence: 98%
See 2 more Smart Citations
“…Reactions with GEDT values below 0.05 e correspond to non-polar processes, while values above 0.20 e correspond to polar processes. Very recently, organic reactions have been classified as forward electron density flux (FEDF) and reverse electron density flux (REDF) reactions, depending on the direction of the flux of the electron density at the TS [28]. Non-polar reactions are classified as null electron density flux (NEDF) reactions [29].…”
Section: Introductionmentioning
confidence: 99%